The power of the word: scripture and the rhetoric of empire - Schüssler Fiorenza, Elisabeth (Fortress Press, 2007)
Introduction: The rhetoric of empire -- Empire studies as a new field in biblical studies -- A radical democratic ethos -- A critical political feminist hermeneutics -- Situating the argument of this book -- The power of Scripture and the rhetoric of empire -- Empire as the context of Scripture today -- Reshaping biblical thelogical studies -- Empire and ekklesia -- A radical democratic imagination : the ekklsia of women -- Debating Paul in the ekklsia of women -- Toward a critical feminist decolonizing interpretation -- Postcolonial criticism and feminist criticism -- A decolonizing interpretation of the book of Revelation -- Empire and the rhetoric of subordination -- The ethos of kyriarchy : intersecting discourses of domination -- A detoxifying/decolonizing reading of 1 Peter -- The rhetoric of empire and G*G-talk : decolonizing the divine -- Feminist critique of androcentric G*D language -- Kyriocentric G*D language : the language of empire -- Transforming biblical studies -- The discipline of biblical studies -- Transforming biblical studies